The Ancient Greek adjective: semantic and grammatical features - Куйбіда, Христина Ігорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article reveals the essence of an Ancient Greek adjective as a separate part of speech. Thus, the substantive nature of an adjective was examined, including the historical process of its separation as an independent part of speech, with a consequent emphasis on the inseparability of adjectives and nouns by external signs in Ancient Greek. The analysis of the Greek adjectives was made on the grounds of their semantics, morphological features, syntactic functions. The semantic analysis was based on the studying of such concepts as the categorial, word-building and lexical meaning. The categorial meaning is the attribution of an adjective. The smaller semantic-grammatical groups (qualitative, relative and possessive adjectives) were learnt with regard to word formation and lexical motivation. Word-building and lexical meanings were studied basing on the division of adjectives into primary units and derivatives. The meaning of a derivative is interpreted both: due to the analysis of its structure (paying a special attention to the compound units, which are mainly formed on the basis of word combinations), and due as to the relation (strong, weak, metaphorical) of the general meaning of a derivative with the meaning of its components. The word-formation meaning of such units, therefore, is syntagmatic. Their lexical semantics depend also on the context. The basic morphological categories of genus, number and case of a Greek adjective simultaneously indicates its semantic dependence on a noun. The category of degrees of comparison was analyzed on terms of morphological means and such syntactic features as left/right-side valence. The main primary (an attribute) and the secondary (as a predicative) syntactic adjective functions are equally realized in preposition or postposition to the noun in Ancient Greek.